2021
DOI: 10.1007/s12185-021-03173-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular spectrum of α- and β-globin gene mutations in Hainan, China

Abstract: Background: Thalassemia is one of the most prevalent inherited single gene diseases. Prevention of βthalassemia through prenatal diagnosis is the one of the most effective and direct approach to control the spread of this life-threatening disease. This study aims to determine the prenatal diagnosis of αthalassemia and β-thalassemia in 3049 families among eighteen regions of Hainan Province using molecular diagnosis.Methods: This study enrolled a total of 3049 couples and their fetuses at The First A liated Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
5
1
Order By: Relevance
“…Ethnic differences may also play a significant role in genetic differences, so we also analyzed thalassemia genotypes in the Han and the minority ethnic groups. In the present study, 74.1% of -- SEA /αα carriers were the Han people, and 19.7% were the Li people, which is consistent with previous studies ( 11 , 28 ), indicating that the -- SEA /αα mutation is more common in the Han than the Li people.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Ethnic differences may also play a significant role in genetic differences, so we also analyzed thalassemia genotypes in the Han and the minority ethnic groups. In the present study, 74.1% of -- SEA /αα carriers were the Han people, and 19.7% were the Li people, which is consistent with previous studies ( 11 , 28 ), indicating that the -- SEA /αα mutation is more common in the Han than the Li people.…”
Section: Discussionsupporting
confidence: 92%
“…The most common mutations are β CD41−42 , β CD17 , β IVS−II−654 , β −28 M , β CD71−72 , β −26 M , β IVS−I−1 , and β −29 M , and these mutations account for more than 95.0% of all β mutations found in the Chinese population ( 29 ). In the current study, 13 genotypes were detected, and β CD41−42 /β N (69.6%) was the most common β-thalassemia genotype in the southern part of Hainan, which was similar to that in an earlier study ( 28 ) and different from that in another study ( 11 ). The proportion of β CD41−42 (88.0%) among β-thalassemia in the southern part of Hainan was the highest and was higher than those in other provinces of China ( 12 , 16 , 17 , 30 ).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In Southern China, α-thalassemia and β-thalassemia are the main two types observed [ 4 ]. It was reported that the most commonly detected mutation for α-thalassemia was SEA/αα (31.53%); the most common mutation for β-thalassemia was CD41/42 (30.27%) in Hainan province, southernmost China [ 5 ]. The clinical phenotypes of concurrent α- and β-thalassemia depend on how many of the four genes for α globin or two genes for β globin are missing [ 6 ].…”
Section: Introductionmentioning
confidence: 99%